Lead recovery facility used lead-acid car battery recycling : a plant design - Chicombing, Jason D.; Cuasay, Jodel L.; Martin, Wilfredo M. II.; Yap, Kristian July R. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
The study aims to design a plant on the recovery of lead from used lead-acid car batteries in the Philippines. There is a significant demand of lead both in the global and Philippine setting 71% of the lead produces both for primary and secondary sources are used in the production of car batteries. There is no mining activity of lead in the Philippines, and with increasing demand for lead metal, the design of a plant for recovering lead from car batteries is feasible and has great potential. The production of high purity and low price lead ingots would give a considerable profit to the plant. Lead will be recovered from used lead-acid car batteries which will gathered all around the country. The separation of sulfuric acid, polypropylene plastic, and other metal impurities are facilitated within the plant. The final product that is expected is 25kg lead ingot bars. The plant capacity is approximately 20,000 tons of lead per year with all the proposed processes and equipment designs.The economic status of the designed plant, with positive outcome from various profitability measures are so follows - Net Present Value of Php 359,000,000.00, Internal Rate of Return of 57%, payback period of just 14 months and Return of Investment of 143 percent, the plant is definitely a good project, which will generate a large profit.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Electric batteries -- Recycling; Recycling centers -- Design and construction